The Role of Knowledge Maps in Supporting The Application of Knowledge Management to Improve The Performance of The King Abdulaziz University Council: ‎A Literature Review - Alsharyofi, Maher saif; Ageeli , Prof. Othman Mousa (International Journal of Accounting and Economics Studies, 2025)
This study investigates the role of knowledge maps in supporting the implementation of ‎knowledge management (KM) to improve the performance of the University Council at ‎King Abdulaziz University. As universities navigate complex environments requiring ‎agile decision-making, effective tools are needed to capture, structure, and utilize ‎knowledge. Knowledge maps, as strategic visual tools, bridge explicit and tacit ‎knowledge within institutional contexts, leveraging technologies such as graph ‎databases and visualization software. A mixed-methods approach was employed, ‎integrating descriptive surveys, expert interviews, and focus groups to assess KM ‎awareness and the impact of knowledge mapping on decision-making. Results revealed ‎that while KM is recognized as a valuable asset, its practices remain underutilized due ‎to organizational and technical barriers, such as limited digital infrastructure and cultural ‎resistance. The proposed model integrates knowledge maps into KM processes, ‎utilizing platforms like Neo4j or Gephi to enhance decision flow, reduce redundancy, ‎and foster innovation. This study contributes a practical framework adaptable to ‎academic governance and offers recommendations for embedding knowledge ‎visualization strategies into university councils, with potential applications across ‎diverse institutions. This model also supports economic efficiency by optimizing ‎resource allocation and reducing administrative costs, aligning with the fiscal goals of ‎Saudi Vision 2030. This study contributes a practical framework adaptable to academic ‎governance and offers recommendations for embedding knowledge visualization ‎strategies into university councils, with potential applications across diverse institutions‎.
Keywords: Knowledge Maps; Knowledge Management; University Council; Performance ‎Improvement; Higher Education Governance; Saudi Arabia.